Paediatric donation after circulatory determined death heart transplantation using donor normothermic regional perfusion and ex situ heart perfusion: A case report. (4th July 2019) - Khushnood, Abbas; Butt, Tanveer A.; Jungschleger, Jerome; Henderson, Paul; Smith, Jonathan H.; De Rita, Fabrizio; Nassar, Mohamed; Page, Aravinda; Messer, Simon; Large, Stephen; Dark, John H.; Parry, Gareth; et al.
Abstract: This is a report of a unique DCD paediatric heart transplant whereby normothermic regional perfusion was used to assess DCD heart function after death followed by ex situ heart perfusion of the graft during transportation from donor to recipient hospitals. The DCD donor was a 9‐year‐old boy weighing 84 kg. The recipient was 7‐year‐old boy with failing Fontan circulation and weighed 23 kg. It was an ABO‐compatible heart transplantation. The DCD heart was reperfused and assessed using normothermic regional perfusion followed by portable ex situ heart perfusion during transportation. The orthotopic heart transplantation was successful with good graft function and no evidence of rejection on endomyocardial biopsy at 30 days post‐transplant. At 1‐year follow‐up, excellent graft function is maintained, and he is attending school with a good quality of life. DCD heart transplantation in children is a promising solution to reducing paediatric waiting times. The case demonstrates the feasibility of using normothermic regional perfusion in the donor and ex situ heart perfusion during graft transportation. This combination allowed a functional assessment whilst minimizing warm ischaemia resulting in a successful outcome. More research and long‐term follow‐up are needed in order to benefit from the huge potential that paediatric DCD heart transplantation has to offer.